DESIGN OF AN ARDUINO-BASED WATER UTILIZATION MONITORING SYSTEM FOR PUBLIC WATER SUPPLY COMPANIES - Irana Dewi; Rudi Arif Candra; Erwinsyah Sipahutar; Arie Budiansyah (Politeknik Aceh Selatan, 2025)
This research presents the design and implementation of an Arduino-based water utilization monitoring system tailored for public water supply companies (PDAM) in Indonesia. The system integrates various sensors, including turbidity, pH, temperature, and electrical conductivity sensors, to effectively monitor water quality and usage in real-time. Utilizing an Arduino microcontroller as the central processing unit, the system automates data collection and processing, providing valuable insights into water conditions and consumption patterns. The incorporation of IoT technology and wireless communication modules enables remote monitoring and control, enhancing operational efficiency and user engagement. The device features a water flow sensor and a digital water meter, with data displayed on an LCD screen, allowing users to track their water consumption easily. Additionally, an alarm system alerts users when water usage approaches a predefined maximum limit, promoting water conservation. The findings indicate that the system operates effectively within specified flow rates, demonstrating its potential as a cost-effective solution for improving water management practices in public water supply sectors. Future enhancements may include internet-based monitoring capabilities and backup power solution This research presents the design and implementation of an Arduino-based water utilization monitoring system tailored for public water supply companies (PDAM) in Indonesia. The system integrates various sensors, including turbidity, pH, temperature, and electrical conductivity sensors, to effectively monitor water quality and usage in real-time. Utilizing an Arduino microcontroller as the central processing unit, the system automates data collection and processing, providing valuable insights into water conditions and consumption patterns.